Disiplin Kerja, Motivasi Kerja, dan Lingkungan Kerja Terhadap Produktivitas Kerja Pegawai - Markus Markus; Titi Hasanah; M Pahlan (IPM2KPE, 2023)
This study aims to determine the effect of work discipline, work motivation, and work environment on employee work productivity at the Research and Development Agency of Lahat Regency. This research method is descriptive quantitative. The population in this study were employees at the Development Agency Office, totaling 32 employees. The sampling technique used a saturated census technique with a sample of 32 respondents. The data analysis technique in this study was multiple linear regression using the SPSS 24 program. The results showed, a) showing the effect of work discipline on work productivity, obtaining a Sig value of 0.019 <0.05; b) testing the effect of work motivation on work productivity, the value obtained is Sig 0.000 <0.05; c) testing the effect of the work environment on work productivity variables, obtained a Sig value of 0.024 <0.05; d) the results of the F test show a Sig value of 0.000 <0.05. In conclusion, the variables of motivation, work environment, and work discipline have an effect on employee productivity either partially or simultaneously. Keywords: Work Discipline, Work Environment, Motivation, Work Productivity